Les constructions sociales de la sexualite - Bozon, Michel; Leridon, Henri (Population (French Edition), 1993)
Keywords: 1900-1999; approches et analyses; cours; discipline; premier cycle; production des savoirs; périodes historiques; rapports sociaux de sexe; sciences humaines; sciences sociales; sex1183; sexologie; sexualité; thématiques; épistémologie

Des outils pour écrire le corps - Centre de création industrielle (Paris); Centre national d'art et de culture Georges Pompidou (Paris); de Certeau, Michel (Traverses, 1993)
Publisher: Centre Georges Pompidou
Keywords: corps; cours; discipline; lit4700; premier cycle; sciences humaines; sociologie; sofia; thématiques

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail

«Débat». Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992 - Farge, Arlette; Perrot, Michelle (Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992, 1993)
Commencée fin 1987, « L’histoire des femmes en Occident » vient de s’achever. Ce travail collectif international d’une grande ampleur - 5 volumes, 3 000 pages écrites par 72 auteurs - constitue à ce jour l’effort le plus achevé pour affirmer la légitimité d’un champ de recherche : l’approche sexuée de l’histoire de nos sociétés. Publiée en 9 langues, cette entreprise a suscité aussitôt un immense intérêt, signe incontestable d’une demande sociale forte. Mais cette approche historique pose beaucoup de questions : sur la pertinence de la chronologie classique, sur la notion d’Occident et son étroitesse, sur la validité des sources, sur la fonction des images, sur la difficulté à saisir autre chose qu’une représentation construite majoritairement par les hommes, sur le consentement des femmes à leur rôle, sur la notion de pouvoirs, sur celle de progrès... Prolongement critique de « L’histoire des femmes en Occident », le colloque « Femmes et Histoire » est la manifestation d’une réflexion ouverte et actuelle qui ne demande qu’à se poursuivre.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; inégalités; occident; premier cycle; rapports sociaux de sexe; sciences humaines; sexisme; systèmes d'oppressions; thématiques

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Section: 1 v. (xi-276 p.) ; 23 cm
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Déclaration des droits de la femme et de la citoyenne - Gouges, Olympe de (Écrits politiques 1788-1791, 1993)
Première publication 1791
Keywords: 1700-1799; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; histoire et politique; incontournable; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Écrits politiques 1788-1791 - Gouges, Olympe de (Côté-femmes, 1993)
Je meurs, mon cher fils, victime de mon idolâtrie pour la patrie et pour le peuple. Ses ennemis, sous le spécieux masque du républicanisme, m'ont conduite sans remords à l'échafaud..." Ainsi commence la dernière lettre qu'Olympe de Gouges adressa à son fils alors qu'elle était enfermée à la Conciergerie dans la cellule des condamnées à mort. A cause de la pluie qui ne cessa pas de la matinée, l'exécution eut lieu dans l'après-midi du 3 novembre 1793.Š Avec des documents inédits à l'appui, Olivier Blanc nous fait revivre, dans sa préface, l'engrenage de l'arrestation et du procès d'Olympe de Gouges, l'auteur de la Déclaration des droits de la femme et de la citoyenne.
Première publication 1791
Keywords: 1700-1799; approches et analyses; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; incontournable; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Wild desires & mistaken identities: lesbianism and psychoanalysis - O'Connor, Noreen; Ryan, Joanna (Columbia University Press, 1993)
This groundbreaking book provides a challenging exploration of psychoanalytic ideas about lesbians and lesbianism. Based on the authors' clinical experience as psychoanalytic psychotherapists, it offers a new and thoughtful framework that does not inevitably pathologise or universalise all lesbianism. A wide range of psychoanalytic ideas are surveyed, from Freud, Deutsch and Jung to Lacan and contemporary object-relations theorists. Questions on sexual identity, sexual desire and gender identity, of transference and countertransference, and also of institutional practices in relation to training, are all critically - and stimunlatingly - addressed.
Section: 315 p.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; désir lesbien; lesbianisme; premier cycle; psychanalyse; sciences humaines; sexualité; soc2014; thématiques

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Libération des femmes: les années-mouvement - Picq, Françoise (Ed. du Seuil, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Section: 380 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; MLF; approches et analyses; cours; discipline; droits des femmes*; europe; france; féminisme matérialiste; histoire; militance; patriarcat; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Mais qu’est-ce qu’elles disent ? - Picq, Françoise (Libération des femmes: les années-mouvement, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Section: 380 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; inégalités; militance; mouvements de femmes*; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques

Formation de l'État et politiques sociales aux Etats-Unis - Skocpol, Theda (Actes de la recherche en sciences sociales, 1993)
Les Américains éprouvent une certaine méfiance à l'égard de la puissance de l'Etat. Cependant, si l'on analyse l'histoire du développement du pays, on constate que les Etats-Unis ont toujours eu "un Etat". Les changements qui ont affecté l'Etat américain -passé d'un Etat fédéral, non bureaucratique, "Etat de tribunaux et de partis" au XIXe siècle, à un Etat fédéral, partiellement partiellement bureaucratisé, orienté vers l'action en faveur de groupes d'intérêts particuliers au XXe siècle -permettent de comprendre les différentes phases et les modalités de la politique sociale américaine. Les Etats-Unis n'ont pas développé un Etat-providence qui, comme en Europe, assure la protection sociale des ouvriers et de tous les citoyens. Entre 1870 et 1920, la politique sociale des Etats-Unis s'est développée principalement en faveur des anciens combattants et des mères de famille ; après 1930, elle a porté surtout sur la mise en place d'un système d'assurance vieillesse pour les retraités. Les institutions politiques américaines ont favorisé le développement de dépenses sociales importantes pour des groupes sociaux qui ne sont pas les plus démunis.
Keywords: 1800-1899; 1900-1999; amériques; cours; discipline; his4443; histoire et politique; maternité; politique américaine; politiques publiques; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; thématiques; états-unis